"Double-punch" strategy against triple-negative breast cancer via a synergistic therapy of magneto-mechanical force enhancing NIR-II hypothermal ablation. (December 2022) - Du, Hui; Yang, Fang; Yao, Chenyang; Lv, Wenhao; Peng, Hao; Stanciu, Stefan G.; Stenmark, Harald A.; Song, Young Min; Jiang, Bo; Wu, Aiguo
Abstract: Triple-negative breast cancer (TNBC) is a form of breast cancer that is more aggressive and harder to treat than others, with a higher probability of relapse. Its nefarious capabilities for migrating and invading other parts of the body together with the current lack of clinically established effective therapies account for a low survival rate. In this work, we demonstrate the in-tandem use of two complementary therapeutic routes to effectively combat TNBC. A versatile magnetic-photothermal converter (MPC) consisting of zinc-doped ferrite nanoparticles and polyethene glycol, is shown to display excellent therapeutic efficiency, being capable to fight TNBC via two distinct routes: magneto-mechanical force (MMF) and near-infrared-II (NIR-II) hypothermal ablation. The combined use of these two complementary and synergistic therapies, which are less aggressive to the human body compared to conventional chemotherapeutic approaches, results in the splendid suppression of TNBC migration and invasion. Remotely controlling the MPCs by an external magnetic field, results in cellular MMF effects that cause direct mechanical destruction to the cancer cell membrane, leading to its necrosis. Furthermore, the MMF disrupts intracellular lysosomes, thereby triggering the release of large amounts of protein hydrolases, which induce intracellular oxidative stress, and accelerate the induction of apoptosis. Complementing the therapeutic approach based on MMF, the excellent photothermal performance of the MPC in the NIR-II region (1064 nm) is exploited to enable effective hypothermal ablation of the tumours, which can be achieved in deep tissue layers. The proposed multifunctional nanocomposites, together with the demonstrated "double-punch" therapeutic approach, hold significant potential to pave the way for future cutting-edge weapons against the dreadful TNBC.